Alkoxy cyanoacrylate-based nanoparticles with stealth and brain-targeting properties. (7th February 2022) - Liu, Jimin; Li, Yunfeng; Liu, Shan; Zhang, Yi; Luo, Yuan; Yang, Yang; Zhuang, Xiaomei; Wang, Xuanzhi; Zhao, Baoquan; Xu, Tao; Xu, Liang
Abstract: Nanoparticles (NPs) with 'stealth' properties have been designed to decrease the phagocytosis of such particles by mononuclear phagocytes and to protect them from enzymatic degradation, thus improving circulation time and bioavailability after intravenous administration. Brain-targeting modifications endow NPs with the capacity to cross the blood–brain barrier, facilitating chemotherapy for brain diseases such as glioma. In this study, newly designed alkoxy cyanoacrylate (CA)-based NPs with stealth and brain-targeting properties were synthesised and evaluated. The monomers for NP core polymerisation were chemically modified to hydrophilic short alkoxy structure for stealth purposes and coated with polysorbate-80 for brain targeting. Two monomers (2-methoxyethyl CA and 2-(2-methoxyethyl)ethyl CA) were used to create NP2 and NP3, respectively. Both NPs were successfully loaded with anti-sense oligonucleotide (ASON) of transforming growth factor beta 2. Compared to traditional n-butyl CA-based ASON–NP1, ASON–NP3 was found to decrease phagocytosis by mononuclear macrophages (RAW264.7) and to increase cellular uptake by cancer cells. ASON–NP3 showed definite brain targeting and anti-cancer effects. This work provides a potential new strategy for preparing stealth NPs core, providing a new NP vehicle for clinical drug delivery that may be targeted to the brain and circulates in the blood for an extended period of time.